Borate birefringent crystal, growth method and application thereof

The growth of Ba2MgTb2(BO3)4 borate birefringent crystals by solvent thermal method solves the problem of low transmittance in the ultraviolet and deep ultraviolet bands of existing materials, achieves the growth of high-quality crystals and excellent optical properties, and meets the needs of the fields of ultraviolet and deep ultraviolet optical.

CN119615367APending Publication Date: 2025-03-14NEW MATERIAL INST OF SHANDONG ACADEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411908059.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing birefringent crystal materials have low transmittance in the ultraviolet and deep ultraviolet bands, and it is difficult to grow high-quality crystals, which cannot meet the needs of the field of ultraviolet and deep ultraviolet optical.

Method used

The Ba2MgTb2(BO3)4 borate birefringent crystals were grown by solvothermal method. By controlling the pH value of the solution between 6.2 and 6.5, the heating rate was adjusted to 10-20℃/h and the cooling rate was 1-2℃/h, and the growth conditions of the crystal were optimized.

Benefits of technology

The growth of high-quality borate birefringent crystals with excellent transmittance and high birefringence coefficient in the ultraviolet and deep ultraviolet bands is achieved, which improves the purity and processing convenience of the crystals, and meets the needs of the field of ultraviolet and deep ultraviolet optical.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615367A_ABST
    Figure CN119615367A_ABST
Patent Text Reader

Abstract

The invention relates to the field of birefringent crystals, in particular to a borate birefringent crystal, a growth method and application thereof. The preparation method comprises the following steps: taking terbium acetylacetonate, magnesium chloride and barium acetate according to a molar ratio, pouring the terbium acetylacetonate, the magnesium chloride and the barium acetate into deionized water to prepare a solution, adjusting the pH value of the solution by using a hydrochloric acid solution, heating to 200-300 DEG C at a heating speed of 10-20 DEG C / h, and carrying out a constant-temperature reaction for 12-24 hours to obtain the terbium acetylacetonate-magnesium chloride-barium acetate composite material. Cooling to room temperature at a cooling speed of 1-2 DEG C / h, taking out the crystal, and washing the crystal with a sodium hydroxide solution, absolute ethyl alcohol and deionized water to obtain a borate birefringent crystal; the obtained borate birefringent crystal solves the problem that an existing birefringent crystal material at the ultraviolet and deep ultraviolet wave bands is scarce, the growth method is simple, the production cost is low, the physical and mechanical properties are stable and reliable, and the borate birefringent crystal shows excellent transmittance and a high birefringent coefficient within the ultraviolet and deep ultraviolet spectrum range. Meanwhile, good moisture-proof performance is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of birefringent crystals, in particular to a borate birefringent crystal, a growth method and application thereof. Background Art

[0002] As a type of functional material with unique optical properties, birefringent crystal materials play a vital role in the manufacture of optical devices. Such materials are widely used in the manufacture of high-end equipment such as optical circulators, beam shifters, and electro-optical Q switches, significantly improving the performance and efficiency of optical systems. In particular, the key optical device, the polarization prism, can efficiently separate and control the polarization state of light by cleverly utilizing the properties of birefringent crystals, and has become an indispensable core component in the fields of optical fiber communications, laser modulation, and the like.

[0003] High-quality polarized light prisms require that the birefringent crystals used must have many excellent properties, including significant birefringence effect, wide transmission band, excellent crystal growth habits, excellent physical and chemical stability, and high laser damage threshold (LDT). With the continuous advancement of laser technology, especially the increasing application in the ultraviolet and deep ultraviolet bands, the demand for optical materials with both high birefringence and excellent deep ultraviolet transmission performance has become more urgent.

[0004] There are many types of birefringent crystals currently circulating in the market, among which CaCO3, YVO4, TiO2, LiNbO3 and α-BBO are particularly prominent. CaCO3 crystals are known for their wide light transmission range of 350 to 2300 nanometers and a birefringence of up to 0.17 at a wavelength of 532 nanometers. Unfortunately, this crystal mainly relies on natural minerals, and the artificial synthesis technology is not yet mature and difficult. YVO4 crystals show excellent birefringence performance at a wavelength of 633 nanometers, with a birefringence of up to 0.22, but its light transmission range is limited to 400 to 5000 nanometers, which cannot meet the application requirements of the ultraviolet band. Although TiO2 crystals have the highest birefringence of all crystals, due to their extremely high hardness and complex processing process, they cannot be used in the ultraviolet band, and their light transmission range is also limited to between 400 and 5000 nanometers. The light transmission range of LiNbO3 crystals is 420 to 5200 nanometers, which is also unable to enter the ultraviolet band. As for α-BBO crystal, although it has a large birefringence and a wide transmittance range, and exhibits good transmission performance in the ultraviolet band, it is prone to phase change during the growth process, has a tendency to deliquesce and cleave, and its thermal expansion is anisotropic, which makes the crystal easy to crack during processing, thus seriously affecting the yield and utilization rate of the crystal, limiting its wide application.

[0005] In view of the limitations of existing materials, researchers have begun to actively explore new birefringent crystal materials with greater potential. Borates are considered to be highly promising candidate materials in the ultraviolet and deep ultraviolet fields due to their specific short ultraviolet cutoff edges and high structural diversity. In borate materials, the BO3 triangle or BO4 tetrahedral structural units formed by B atoms and O atoms can be further polymerized into infinite chains, sheets and networks, thus giving the materials rich structural and multifunctional properties. In addition, borate materials generally have a wide transparency range, high laser damage threshold, and excellent chemical and thermal stability, which gives them broad application prospects in the field of optics.

[0006] Birefringent crystal materials have broad application prospects in the field of optics, and borates, as a new type of material with unique advantages and potential, are becoming the focus of scientific researchers.

[0007] In recent years, a variety of borate birefringent crystals have been discovered, but their low transmittance in the ultraviolet and deep ultraviolet regions limits their use. In addition, due to the limitations of growth characteristics, it is difficult to grow large and high-quality crystals. Therefore, it is particularly urgent and important to develop a new type of birefringent crystal suitable for the ultraviolet and deep ultraviolet bands. Summary of the invention

[0008] The present invention aims to solve the problems in the prior art that high-quality birefringent crystals are scarce and cannot effectively cover the ultraviolet and deep ultraviolet bands, and provides a borate birefringent crystal and a growth method and application thereof.

[0009] The first object of the present invention is to provide a borate birefringent crystal, the chemical formula of which is Ba2MgTb2(BO3)4, belonging to the orthorhombic system, the Pbca space group, and the unit cell parameters are The size of the borate birefringent crystal is 12×10×3 mm.

[0010] The second object of the present invention is to provide a method for growing a borate birefringent crystal, wherein the growth method is a solvothermal method, and the specific steps are:

[0011] Step 1: According to terbium acetylacetonate (C 15 H 21 The molar ratio of terbium acetylacetonate (Tb) to magnesium chloride (MgCl2) to barium acetate ((CH3COO)2Ba) is 2.05:1:2 and the amount of terbium acetylacetonate is slightly larger to ensure the complete reaction.

[0012] Step 2: Weigh terbium acetylacetonate (C 15 H 21O6Tb), magnesium chloride (MgCl2) and barium acetate ((CH3COO)2Ba) are gradually poured into deionized water until the solution reaches a saturated state to obtain a saturated solution, and the pH value of the saturated solution is adjusted with a hydrochloric acid solution; in this application, terbium acetylacetonate (C 15 H 21 O6Tb), magnesium chloride (MgCl2) and barium acetate ((CH3COO)2Ba) are added in an amount to achieve a saturated state of the solution.

[0013] Step 3: First, transfer the saturated solution with adjusted pH value into the autoclave, then seal the autoclave and place it in a furnace for heating. Raise the temperature in the furnace to 200-300℃ at a heating rate of 10-20℃ / h, and react at a constant temperature of 200-300℃ for 12-24 hours to ensure that Ba2MgTb2(BO3)4 crystals can fully and orderly grow. Selecting a suitable heating rate can ensure that the raw materials can react with each other completely and that the pressure in the autoclave does not rise suddenly, so the autoclave explodes due to excessive pressure in the autoclave. The constant temperature reaction temperature depends on the reaction system and the heat resistance of the autoclave. Too high a temperature will damage the lining of the autoclave.

[0014] Step 4. After the isothermal reaction is completed, the temperature in the muffle furnace is reduced to room temperature under the condition of a cooling rate of 1-2°C / h to obtain a crystal; cooling at a cooling rate of 1-2°C / h can effectively promote the orderly growth of the crystal and effectively reduce crystal defects; the cooling rate is an important factor in determining the size of the crystal, the integrity of the crystal shape and the purity of the crystal. The use of a slower cooling rate (cooling rate of 1-2°C / h) in this application helps the crystal grow at a slower rate, thereby allowing more atoms or molecules to be correctly arranged in the crystal structure to form a more complete and uniform crystal. The use of a faster cooling rate (i.e., when the cooling rate is higher than 1-2°C / h) will cause the crystal to grow too fast, forming an undesirable crystal morphology, and even producing defects such as inclusion of mother liquor and void ratio growth. A slower cooling rate helps to reduce the stress inside the crystal and make the crystal structure more stable. A slower cooling rate helps impurities to be excluded or rearranged outside the crystal during the cooling process, thereby improving the purity of the crystal. This step is crucial to promoting the orderly growth of crystals and reducing defects.

[0015] Step 5: First, wash the crystals with sodium hydroxide solution for the first time, then wash them with anhydrous ethanol for the second time, and finally rinse the crystals with deionized water for 2-4 times to obtain borate birefringent crystals (Ba2MgTb2(BO3)4). By washing the crystals with sodium hydroxide solution, anhydrous ethanol and deionized water to remove impurities, higher purity crystals can be obtained.

[0016] Furthermore, the concentration of the hydrochloric acid solution is 4.5 mol / L.

[0017] Further, the pH value of the saturated solution after adjustment with hydrochloric acid is 6.2 to 6.5. Solvothermal method is a method for preparing high-purity crystalline materials. In the process of solvothermal crystal growth, the pH value of the solution is an important influencing factor. The pH value of the solution is adjusted to acidic, and its mechanism of action is: 1. Promote the growth of specific crystals: borate birefringent crystals have better growth habits in an acidic environment. By adjusting the pH value of the solution to acidic, the growth of borate birefringent crystals can be facilitated. 2. Control the activity of impurities: In acidic solutions, the activity of impurities will be passivated, thereby reducing the adverse effects of impurities on crystal growth.

[0018] Furthermore, the filling amount of the saturated solution in step 3 is 60%-75% of the total volume of the autoclave, which can effectively improve the efficiency and safety of the isothermal reaction.

[0019] Furthermore, the concentration of the sodium hydroxide solution is 1.2 mol / L.

[0020] Furthermore, the volume fraction of anhydrous ethanol is 45%.

[0021] Further, the preparation method comprises the following specific steps:

[0022] (1) First, accurately weigh terbium acetylacetonate (C 15 H 21 O6Tb), magnesium chloride (MgCl2) and barium acetate ((CH3COO)2Ba), ensuring that the molar ratio of the three is 2.05:1:2. Secondly, terbium acetylacetonate, magnesium chloride and barium acetate are dissolved in deionized water, and under the continuous and uniform stirring of a magnetic stirrer, until the solution reaches a saturated state, and again with a hydrochloric acid solution with a concentration of 4.5mol / L as a titrant, the pH value of the saturated solution is finely adjusted to ensure that the pH value of the saturated solution is stably maintained in an appropriate range of 6.2 to 6.5;

[0023] (2) transferring the saturated solution prepared in step (1) into a Teflon-lined autoclave, ensuring that the filling amount of the saturated solution accounts for between 60% and 75% of the total volume of the autoclave;

[0024] (3) After sealing the autoclave, place it in a muffle furnace for heating. At a heating rate of 10-20°C / h, gradually increase the temperature to a constant temperature range of 200 to 300°C. Under this temperature condition, maintain the constant temperature reaction for 12 to 24 hours;

[0025] (4) After the isothermal reaction is completed, the temperature is lowered at a rate of 1-2°C / h;

[0026] (5) After the autoclave is cooled to room temperature, the obtained crystals are taken out and firstly cleaned with a 1.2 mol / L sodium hydroxide solution; secondly, a secondary cleaning is performed with anhydrous ethanol with a volume fraction of 45% to remove residual organic impurities; finally, a thorough rinse is performed with deionized water, and the rinse is repeated 2-4 times to ensure that all impurities are effectively removed. After the above cleaning steps, a borate birefringent crystal (Ba2MgTb2(BO3)4) is obtained. The borate birefringent crystal (Ba2MgTb2(BO3)4) prepared by the present application has good purity and high quality.

[0027] The third object of the present invention is to apply borate birefringent crystals in the optical field of ultraviolet and deep ultraviolet bands.

[0028] The beneficial effects of the present invention are:

[0029] The invention provides a borate birefringent crystal. The borate birefringent crystal solves the problem of scarcity of existing birefringent crystal materials in ultraviolet and deep ultraviolet bands.

[0030] The invention provides a high-quality borate birefringent crystal. The crystal is insoluble in water and is easy to process and cut, thereby enhancing the practical value of the borate birefringent crystal.

[0031] The present invention provides a borate birefringent crystal, which has great industrial application prospects in the field of optical communication devices, can effectively meet the urgent needs of ultraviolet and deep ultraviolet birefringence technology, and provide strong support for the rapid development of related industries.

[0032] The present invention provides a method for growing a borate birefringent crystal. The method is simple, the production cost is low, the physical and mechanical properties are stable and reliable, and the crystal exhibits excellent transmittance and high birefringence coefficient in the ultraviolet and deep ultraviolet spectral ranges, while having good moisture resistance.

[0033] The invention provides a method for growing a borate birefringent crystal, optimizes parameters, adopts a heating rate of 10-20°C / h, a cooling rate of 1-2°C / h, and a pH value of 6.2 to 6.5, thereby ensuring product quality and normal operation of the process. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a crystal picture of the borate birefringent crystal obtained in Example 1;

[0035] Figure 2 is the transmission spectrum of the borate birefringent crystal obtained in Example 1;

[0036] Figure 3 This is the birefringence spectrum of the borate birefringent crystal prepared in Example 1. DETAILED DESCRIPTION

[0037] In order to better understand the present invention, the technical solution of the present invention is described in detail with specific examples below, but the present invention is not limited thereto.

[0038] Other raw materials used in the present invention are all commercially available products.

[0039] Example 1 A method for growing a borate birefringent crystal

[0040] Step 1: According to terbium acetylacetonate (C 15 H 21 O6Tb): magnesium chloride (MgCl2): barium acetate ((CH3COO)2Ba) in a molar ratio of 2.05:1:2 are weighed;

[0041] Step 2: First weigh terbium acetylacetonate (C 15 H 21 O6Tb), magnesium chloride (MgCl2) and barium acetate ((CH3COO)2Ba), followed by terbium acetylacetonate (C 15 H 21 O6Tb), magnesium chloride (MgCl2) and barium acetate ((CH3COO)2Ba) are poured into deionized water to prepare a solution, the solution is placed in a magnetic stirrer and stirred evenly until the solution reaches a saturated state to obtain a saturated solution, and a hydrochloric acid solution with a concentration of 4.5 mol / L is used as a titrant to adjust the pH value of the saturated solution to 6.2;

[0042] Step 3: first, transfer the saturated solution into a Teflon-lined autoclave, the filling amount of the saturated solution is 60% of the total volume of the autoclave, and then seal the autoclave and place it in a muffle furnace for heating. The temperature in the muffle furnace is raised to 200° C. at a heating rate of 10° C. / h, and the reaction is carried out at a constant temperature for 12 hours at 200° C.;

[0043] Step 4: After the constant temperature reaction is completed, the temperature in the muffle furnace is lowered to room temperature at a cooling rate of 1°C / h to obtain a crystal; cooling at a cooling rate of 1°C / h can effectively promote the orderly growth of the crystal and effectively reduce crystal defects;

[0044] Step 5: First, wash the crystal with a sodium hydroxide solution having a concentration of 1.2 mol / L, then wash the crystal with anhydrous ethanol having a volume fraction of 45% for a second time, and finally rinse the crystal with deionized water for two times to obtain a borate birefringent crystal.

[0045] The borate birefringent crystal prepared by the present invention has a chemical formula of Ba2MgTb2(BO3)4, belongs to the orthorhombic system, has a Pbca space group, and has a unit cell parameter of

[0046] The size of the borate birefringent crystal prepared by the present invention is 12×10×3 mm. Figure 1 shown.

[0047] Example 2 A method for growing a borate birefringent crystal

[0048] Step 1: According to terbium acetylacetonate (C 15 H 21 O6Tb): magnesium chloride (MgCl2): barium acetate ((CH3COO)2Ba) in a molar ratio of 2.05:1:2 are weighed;

[0049] Step 2: First weigh terbium acetylacetonate (C 15 H 21 O6Tb), magnesium chloride (MgCl2) and barium acetate ((CH3COO)2Ba), followed by terbium acetylacetonate (C 15 H 21 O6Tb), magnesium chloride (MgCl2) and barium acetate ((CH3COO)2Ba) are poured into deionized water to prepare a solution, the solution is placed in a magnetic stirrer and stirred evenly until the solution reaches a saturated state to obtain a saturated solution, and a hydrochloric acid solution with a concentration of 4.5 mol / L is used as a titrant to adjust the pH value of the saturated solution to 6.4;

[0050] Step 3, first transfer the saturated solution into a Teflon-lined autoclave, the filling amount of the saturated solution is 67% of the total volume of the autoclave, and then seal the autoclave and place it in a muffle furnace for heating, and raise the temperature in the muffle furnace to 250°C at a heating rate of 15°C / h, and react at a constant temperature of 250°C for 18 hours;

[0051] Step 4: After the isothermal reaction is completed, the temperature in the muffle furnace is lowered to room temperature at a cooling rate of 1.5°C / h to obtain a crystal; cooling at a cooling rate of 1.5°C / h can effectively promote the orderly growth of the crystal and effectively reduce crystal defects;

[0052] Step 5: First, clean the crystal with a 1.2 mol / L sodium hydroxide solution, then clean the crystal with 45% anhydrous ethanol, and finally rinse the crystal with deionized water for 3 times to obtain a borate birefringent crystal with a chemical formula of Ba2MgTb2(BO3)4.

[0053] Example 3 A method for growing a borate birefringent crystal

[0054] Step 1: According to terbium acetylacetonate (C 15 H 21O6Tb): magnesium chloride (MgCl2): barium acetate ((CH3COO)2Ba) in a molar ratio of 2.05:1:2 are weighed;

[0055] Step 2: First weigh terbium acetylacetonate (C 15 H 21 O6Tb), magnesium chloride (MgCl2) and barium acetate ((CH3COO)2Ba), followed by terbium acetylacetonate (C 15 H 21 O6Tb), magnesium chloride (MgCl2) and barium acetate ((CH3COO)2Ba) are poured into deionized water to prepare a solution, the solution is placed in a magnetic stirrer and stirred evenly until the solution reaches a saturated state to obtain a saturated solution, and a hydrochloric acid solution with a concentration of 4.5 mol / L is used as a titrant to adjust the pH value of the saturated solution to 6.5;

[0056] Step 3: first, transfer the saturated solution into a Teflon-lined autoclave, the filling amount of the saturated solution is 75% of the total volume of the autoclave, and then seal the autoclave and place it in a muffle furnace for heating. The temperature in the muffle furnace is raised to 300° C. at a heating rate of 20° C. / h, and the reaction is carried out at a constant temperature of 300° C. for 24 hours;

[0057] Step 4: After the constant temperature reaction is completed, the temperature in the muffle furnace is lowered to room temperature at a cooling rate of 2°C / h to obtain a crystal; cooling at a cooling rate of 2°C / h can effectively promote the orderly growth of the crystal and effectively reduce crystal defects;

[0058] Step 5: First, clean the crystal with a 1.2 mol / L sodium hydroxide solution, then clean the crystal with 45% anhydrous ethanol, and finally rinse the crystal with deionized water for 4 times to obtain a borate birefringent crystal with a chemical formula of Ba2MgTb2(BO3)4.

[0059] Comparative Example 1 A method for growing a borate birefringent crystal

[0060] Step 1: According to terbium acetylacetonate (C 15 H 21 O6Tb): magnesium chloride (MgCl2): barium acetate ((CH3COO)2Ba) in a molar ratio of 2.05:1:2 are weighed;

[0061] Step 2: First weigh terbium acetylacetonate (C 15 H 21 O6Tb), magnesium chloride (MgCl2) and barium acetate ((CH3COO)2Ba), followed by terbium acetylacetonate (C 15 H 21O6Tb), magnesium chloride (MgCl2) and barium acetate ((CH3COO)2Ba) are poured into deionized water to prepare a solution, the solution is placed in a magnetic stirrer and stirred evenly until the solution reaches a saturated state to obtain a saturated solution, and a hydrochloric acid solution with a concentration of 4.0 mol / L is used as a titrant to adjust the pH value of the saturated solution to 6.0;

[0062] Step 3, first transfer the saturated solution into a Teflon-lined autoclave, the filling amount of the saturated solution is 60% of the total volume of the autoclave, and then seal the autoclave and place it in a muffle furnace for heating, raise the temperature in the muffle furnace to 200°C at a heating rate of 10°C / h, and react at a constant temperature of 200°C for 12 hours; the heating rate is 10°C / h;

[0063] Step 4: After the constant temperature reaction is completed, the temperature in the muffle furnace is lowered to room temperature at a cooling rate of 1.5°C / h. No crystal grains are collected after the temperature is lowered to room temperature.

[0064] Comparative Example 2 A method for growing a borate birefringent crystal

[0065] Step 1: According to terbium acetylacetonate (C 15 H 21 Weigh the molar ratio of O6Tb): magnesium chloride (MgCl2): barium acetate ((CH3COO)2Ba) to 2.05:1:2

[0066] Step 2: First weigh terbium acetylacetonate (C 15 H 21 O6Tb), magnesium chloride (MgCl2) and barium acetate ((CH3COO)2Ba), followed by terbium acetylacetonate (C 15 H 21 O6Tb), magnesium chloride (MgCl2) and barium acetate ((CH3COO)2Ba) are poured into deionized water to prepare a solution, the solution is placed in a magnetic stirrer and stirred evenly until the solution reaches a saturated state to obtain a saturated solution, and a hydrochloric acid solution with a concentration of 4.0 mol / L is used as a titrant to adjust the pH value of the saturated solution to 6.3;

[0067] Step 3, first transfer the saturated solution into a Teflon-lined autoclave, the filling amount of the saturated solution is 60% of the total volume of the autoclave, and then seal the autoclave and place it in a muffle furnace for heating, raise the temperature in the muffle furnace to 200°C at a heating rate of 10°C / h, and react at a constant temperature of 200°C for 12 hours; the heating rate is 10°C / h;

[0068] Step 4: After the isothermal reaction is completed, the temperature in the muffle furnace is lowered to room temperature at a cooling rate of 2.5°C / h to obtain crystals;

[0069] Step 5: First, the crystals were washed with a sodium hydroxide solution having a concentration of 1.2 mol / L, then washed with anhydrous ethanol for a second time, and finally washed with deionized water for a third time to obtain crystals. The obtained crystals had inclusions, and the components thereof were mainly CuCl2 and BaCl2, and obvious cracks were observed.

[0070] It can be found from Examples 1-3 and Comparative Examples 1-2 that during the crystal growth process, when the cooling rate is controlled within the range of 1-2°C / h, the quality of the grown crystal is the best. Specifically,

[0071] 1. At a cooling rate of 1°C / h, although the crystals are slightly smaller in size, their crystal form is complete and uniform in size, and the number of internal defects such as dislocations and inclusions is small. At the same time, the purity of the crystals is high, thanks to the slower cooling rate, which helps to effectively remove impurities.

[0072] 2. When the cooling rate is increased to 2℃ / h, the crystals not only have a larger size, but also maintain good crystal integrity. Compared with the cooling rate of 1℃ / h, the growth rate of the crystals has accelerated, but its quality is still maintained at a high level. Although the purity of the crystals may be slightly lower than the level at 1℃ / h, it is still within the acceptable high-quality range.

[0073] 3. In contrast, when the cooling rate is too fast (for example, the cooling rate exceeds 2°C / h), the crystals are larger in size, but the crystal form is incomplete and uneven in size, and the number of internal defects such as dislocations and cracks increases significantly. In addition, the faster cooling rate makes it impossible to effectively remove impurities, which significantly reduces the purity of the crystals.

[0074] In summary, the cooling rate is an important factor in determining the size of the crystal, the integrity of the crystal shape and the purity of the crystal. The use of a slower cooling rate (such as a cooling rate of 1-2°C / h) in the present application helps the crystals grow at a slower rate, thereby allowing more atoms or molecules to be correctly arranged in the crystal structure to form more complete and uniform crystals. The use of a faster cooling rate (i.e., a cooling rate higher than 1-2°C / h) will cause the crystals to grow too fast, forming an undesirable crystal morphology, and even defects such as inclusion of mother liquor and increased porosity. A slower cooling rate helps to reduce the stress inside the crystal and make the crystal structure more stable. A slower cooling rate helps impurities to be excluded or rearranged outside the crystal during the cooling process, thereby improving the purity of the crystal.

[0075] When growing borate birefringent crystals (Ba2MgTb2(BO3)4), hydrochloric acid is used to control the pH value of the saturated solution between 6.2 and 6.5, and other solvents are not used to adjust the pH value. The reasons are:

[0076] The pH value of a solution directly affects the existence form and reactivity of ions in the solution. For a composite oxide crystal such as borate birefringent crystal (Ba2MgTb2(BO3)4), its growth process involves the coordination and reaction of multiple ions. Within a specific pH range (such as pH 6.2-6.5), these ions can exist more stably, which is conducive to the formation of a regular crystal structure.

[0077] Under overly acidic or overly alkaline conditions, too many impurities or by-products will be generated, which will affect the purity and quality of the crystals. By controlling the pH value of the saturated solution between 6.2-6.5, the generation of impurities can be reduced and the purity of the crystals can be ensured.

[0078] Example 6

[0079] The borate birefringent crystal prepared by the invention is applied in the field of optical communication devices.

[0080] The transmission spectrum of the borate birefringent crystal (Ba2MgTb2(BO3)4) prepared in Example 1 was analyzed. The test sample was a polished borate birefringent crystal (Ba2MgTb2(BO3)4) with a thickness of 1.5 mm. The test results are shown in Figure 2. Figure 2 As shown in the figure (transmission spectrum of borate birefringent crystal (Ba2MgTb2(BO3)4)), it can be observed that in the wavelength range of 400 to 2000 nanometers, the transmittance of borate birefringent crystal (Ba2MgTb2(BO3)4) is always maintained above 80%. When the wavelength is close to 280 nanometers, the transmittance of borate birefringent crystal (Ba2MgTb2(BO3)4) can still reach 40%. In addition, the ultraviolet absorption edge of the transmittance of borate birefringent crystal (Ba2MgTb2(BO3)4) is about 203 nanometers, which is close to α-BBO (189 nanometers), indicating that it is suitable for the manufacture of deep ultraviolet optical communication devices.

[0081] The borate birefringent crystal (Ba2MgTb2(BO3)4) prepared in Example 1 was processed into a triangular prism shape, and the refractive index was measured at 12 different wavelengths in the wavelength range of 404.7 nm to 1068 nm. The measurement results are shown in Table 1. The measurement accuracy error of these refractive indices is ±2×10 -4 Then, using the least squares method, combined with the measured n e and n o The Sellmeier dispersion equation is derived from the following formula:

[0082]

[0083] In the above equation, λ represents the wavelength, which is n e and n o The variation of refractive index with wavelength is shown in Figure 3 , at a laser wavelength of 589 nanometers, the ordinary light refractive index n of the borate birefringent crystal (Ba2MgTb2(BO3)4) is o and the extraordinary refractive index n e They are 1.9733 and 1.8899 respectively, and their birefringence is as high as 0.0834, showing good optical properties.

[0084] Table 1 Refractive index at specific wavelengths

[0085] wavelength <![CDATA[n o ]]> <![CDATA[n e ]]> Δn 1.068 1.9329 1.8572 0.0757 0.9592 1.9375 1.8610 0.0765 0.8617 1.9419 1.8645 0.0774 0.8072 1.9457 1.8677 0.0780 0.6943 1.9580 1.8776 0.0804 0.6563 1.9632 1.8818 0.0814 0.5893 1.9733 1.8899 0.0834 0.578 1.9780 1.8937 0.0843 0.5461 1.9866 1.9004 0.0862 0.4962 2.0066 1.9161 0.0905 0.4861 2.0112 1.9196 0.0916 0.4047 2.0716 1.9659 0.1057

[0086] The raw materials listed in the present invention, as well as the upper and lower limits and interval values ​​of the raw materials of the present invention, and the upper and lower limits and interval values ​​of the process parameters can all realize the present invention, and the embodiments are not listed one by one here.

[0087] The above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and changes can be made without departing from the principle of the present invention, and these improvements and changes are also regarded as the protection scope of the present invention.

Claims

1. A borate birefringent crystal with the chemical formula Ba2MgTb2(BO3)4, belonging to the orthorhombic system, Pbca space group, and unit cell parameters 2. The method for growing a borate birefringent crystal according to claim 1, wherein: The growth method is a solvothermal method, and the specific steps are: Step 1, weighing according to the molar ratio of terbium acetylacetonate: magnesium chloride: barium acetate of 2.05:1:2; Step 2: Pour the weighed terbium acetylacetonate, magnesium chloride and barium acetate into deionized water until the solution reaches a saturated state to obtain a saturated solution, and adjust the pH value of the saturated solution with a hydrochloric acid solution; Step 3: first, transfer the saturated solution with adjusted pH value into an autoclave, then seal the autoclave and place it in a furnace for heating, raise the temperature in the furnace to 200-300°C at a heating rate of 10-20°C / h, and react at a constant temperature of 200-300°C for 12-24 hours; Step 4: After the constant temperature reaction is completed, the temperature in the furnace is lowered to room temperature at a cooling rate of 1-2°C / h, and the borate birefringent crystal Ba2MgTb2(BO3)4 is obtained by washing.

3. The method for growing a borate birefringent crystal according to claim 2, characterized in that: The concentration of the hydrochloric acid solution is 4.5 mol / L.

4. The method for growing a borate birefringent crystal according to claim 2, wherein: The pH value of the saturated solution after adjustment with hydrochloric acid is 6.2 to 6.

5.

5. The method for growing a borate birefringent crystal according to claim 2, characterized in that: The filling amount of the saturated solution in step 3 is 60%-75% of the total volume of the autoclave.

6. The method for growing a borate birefringent crystal according to claim 2, wherein: (1) First, weigh terbium acetylacetonate, magnesium chloride and barium acetate to ensure that the molar ratio of the three is 2.05:1:2; secondly, dissolve terbium acetylacetonate, magnesium chloride and barium acetate in deionized water, and stir the solution under continuous and uniform stirring of a magnetic stirrer until the solution reaches a saturated state; and again use a hydrochloric acid solution with a concentration of 4.5 mol / L as a titrant to adjust the pH value of the saturated solution to maintain it in the range of 6.2 to 6.5; (2) transferring the saturated solution prepared in step (1) into a Teflon-lined autoclave, ensuring that the filling amount of the saturated solution accounts for 60% to 75% of the total volume of the autoclave; (3) After sealing the autoclave, place it in a muffle furnace for heating, and gradually increase the temperature to a constant temperature range of 200 to 300° C. at a heating rate of 10 to 20° C. / h. Under this temperature condition, maintain the constant temperature reaction for 12 to 24 hours; (4) After the isothermal reaction is completed, the temperature is lowered at a rate of 1-2°C / h; (5) After the autoclave is cooled to room temperature, the obtained crystals are taken out and firstly cleaned with sodium hydroxide solution; secondly, they are cleaned twice with anhydrous ethanol, and finally, they are repeatedly rinsed with deionized water for 2-4 times. After the above cleaning steps, the borate birefringent crystal Ba2MgTb2(BO3)4 is obtained.

7. The method for growing a borate birefringent crystal according to claim 6, characterized in that: The concentration of the sodium hydroxide solution is 1.2 mol / L.

8. The method for growing a borate birefringent crystal according to claim 6, characterized in that: The volume fraction of the anhydrous ethanol is 45%.

9. Application of the borate birefringent crystal according to any one of claims 1 to 8 in the field of ultraviolet and deep ultraviolet optics.